Pemahaman Mahasiswa tentang Hakikat Sains dalam Pembelajaran menggunakan Model Pembelajaran Mobile-NOS - Khery, Yusran; Nufida, Baiq Asma; Suryati, S.; Rahayu, Sri; Aini, Miftahul (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2019)
[Title: Students' Understanding of the Nature of Science in Learning using the Mobile-NOS Learning Model]. This research aimed to evaluate the influence of the Mobile-NOS model of learning application towards Students' Understanding of the Nature of Science. In the form of pre-experimental research, this study has been carried out by pretest-posttest non-control group design. The research subjects consisted of 27 students participating in the Basic Chemistry II course in the chemical education program of IKIP Mataram Academic Year 2018/2019 collected by saturated sampling. The Nature of Science data was obtained using the Understanding of Nature of Science questionnaire that consists of 39 valid items with very high reliability (r = 0.802) proved by test result to 84 subjects. A paired sample t-test used to analyze the data obtained. The results showed significant enhancement on students' understanding of the nature of science after the Mobile-NOS model of the learning implementation. The value of t count (5.353) is higher than the t table (1.706) in the one-way hypothesis. Based on the results of the study, it can be concluded that the Mobile-NOS learning model influences students' understanding of the nature of science.